Implementation of Religious Moderation Values at Marhalah Tsanawiyah TMI Putra Al-Amien Prenduan Sumenep in 2022 - Musleh Wahid; Muhammad Aziz Fauzi (ATTAQWA: Jurnal Pendidikan Islam dan Anak Usia Dini, 2024)
Religious moderation emphasizes balance, tolerance and justice to avoid extremism and radicalism. This principle supports democracy and the constitution, and values diversity. Education in the values of religious moderation ensures that young people are not exposed to radical ideologies and helps maintain harmony and peace in society. Therefore, the aim of this research is: To find out the value of implementing the value of religious moderation for TMI Al-Amien Prenduan marhalah Tsanawiyah students. to find out how to implement the value of religious moderation for TMI Al-Aimen Prenduan's Marhalah Tsanawiyah Putra students.  This research uses a descriptive qualitative approach with data sourced from primary data and secondary data, as well as data collection techniques used in the form of observations, interviews and documentation, while the data analysis techniques used include data reduction, data presentation and drawing conclusions. The results of research on Islamic education moderation are relevant because the majority of Muslims in Indonesia support democracy and do not conflict with the country's constitution. Moderation in Islam is the key to facing radicalism and aims to maintain compliance with the rules and respect Indonesia's diversity. The principles of justice, balance, and tolerance in Islamic moderation are important for maintaining independence. Moderation education also plays a role in preventing radicalism in the younger generation which is often misunderstood as jihad.